Organizational complexity and corporate governance in major public companies in Brazil - Renata Rouquayrol Assunção; Márcia Martins Mendes De Luca; Alessandra Carvalho de Vasconcelos; Sílvia Maria Dias Pedro Rebouças (Enfoque, 2014)
The complexity of organizations is regarded as the starting point for the separation between control and propriety activities, while corporate governance, which promotes an alignment of interests between the principal and the agent, can be perceived as a means to perfect companies’ controlling devices. In this context, the present study aims at investigating the relation between organizational complexity and corporate governance in 100 major public companies in Brazil, by market value, according to the ranking of the magazine “Exame Melhores e Maiores”, 2012 edition. It is a descriptive research, of quantitative nature, which gathers a sample of 95 companies. For the statistical evaluation of the relation between organizational complexity and corporate governance, factorial analysis and correspondence analysis were applied. The results of the tests indicate that the public companies of greater organizational complexity, despite requiring the adoption of better managing practices, are the ones with lower levels of corporate governance, which suggests that controlling devices inherent to corporate governance can be limited by the level of organizational complexity. Therefore it is concluded that despite the separation of the activities of the principal and the agent have occurred because of organizational complexity, no direct correlation was observed between the level of complexity and governance, which corresponds, in this study, the participation of companies in special segments of BM&FBovespa.